Understanding the future of lithium: Part 1, resource model. (1st October 2019) - Ambrose, Hanjiro; Kendall, Alissa
Abstract: Lithium is a critical energy material in part due to an array of emerging technologies from electric vehicles to renewable energy systems that rely on large‐format lithium ion batteries. Recent growth in demand for lithium is primarily from increased use in batteries, which comprised 46% of total lithium by end use in 2017. These technologies are often deployed to improve environmental sustainability, yet the environmental effects and sustainability of the resources they rely on are often not well understood, especially as demand increases over time. This is the first in a two part article series that together quantify the lithium resource use and its environmental effects over time by coupling a resource production model and life cycle assessment model. In this first part, a novel resource production model is developed to create scenarios of future lithium demand and production characteristics (e.g., timing, location, and ore type). These scenarios are then used to create a life cycle assessment in part two that captures temporal and spatial changes in production systems over time. Results of the resource production model show global lithium resources range from 293 to 527 million metric tons (Mt) of lithium carbonate equivalent (LCE). Global production will likely increase from 237, 000 metric tons LCE in 2018 to 4.4–7.5 Mt LCE/year by 2100. Even with rapidly increasing demand, production from high‐grade brines may satisfy most lithium demand through 2035. Though resources can meet demand through 2100, development of lower grade and unfavorable deposits is likely required after 2050.